Brain-Derived Neurotrophic Factor Is an Important Therapeutic Factor in Mesenchymal Stem Cell Secretions for Treatment of Traumatic Peripheral Pelvic Injuries - Yuan, Xiaoyi; Balog, Brian M.; Lin, Dan Li; Hanzlicek, Brett; Kuang, Mei; Yan, Hao; Majerus, Steve J. A.; Damaser, Margot S. (Frontiers in Cellular Neuroscience, 2022)
Traumatic neuromuscular injury to the pudendal nerve and urethra during childbirth does not regenerate well and contributes to stress urinary incontinence in women. Mesenchymal stem cells (MSCs) can improve neuroregeneration via their secretions, or secretome, which includes brain derived neurotrophic factor (BDNF). In this study, we investigated whether BDNF is a key factor in the secretome of MSCs for facilitation of functional recovery following a dual simulated childbirth injury. BDNF knockdown (KD) MSCs were created using an anti-BDNF shRNA lentivirus vector. A scrambled sequence was used as a transduction control (scrambled). Cells were cultured for 24 hours before media was concentrated 50x to create concentrated conditioned media (CCM) containing MSC secretome. CCM of unmanipulated MSCs were screened for high BDNF expression (high BDNF CCM). Concentrated control media (CM) was created by concentrating media not conditioned by cells. Female Sprague-Dawley rats underwent bilateral pudendal nerve crush and vaginal distension (Injury) or sham injury. One hour and 1 week after injury, sham injured rats received CM and injured rats received CM, high BDNF CCM, KD CCM, or scrambled CCM (300µl intraperitoneally). Three weeks after injury, rats underwent leak point pressure (LPP) and pudendal nerve sensory branch potential (PNSBP) recordings. The urethra and pudendal nerve were harvested for anatomical assessment. ANOVA followed by Student-Newman-Keuls test determined significant differences between groups (p<0.05). BDNF KD CCM had significantly decreased BDNF concentration compared to scrambled CCM, while concentration in high BDNF CCM was significantly increased. LPP was significantly decreased in CM and KD CCM treated animals compared to sham injury, but not with scrambled or high BDNF CCM. PNSBP firing rate showed a significant decrease with CM treatment compared to sham injury. Neuromuscular junctions in the urethral sphincter in KD CCM, scrambled CCM, and high BDNF CCM were healthier than CM treated rats. While anatomical and nerve function tests demonstrate regeneration of the pudendal nerve with any CCM treatment, LPP results suggest it takes longer to recover continence with reduced BDNF in CCM. BDNF in MSC CCM is an important factor for acceleration of recovery from a dual nerve and muscle injury.